THE INFLUENCE OF BRAND AMBASSADOR, BRAND IMAGE WITH CUSTOMER TRUST AS INTERVENING ON PURCHASE DECISION OF SKINTIFIC USERS IN YOGYAKARTA - Nuraisyah Vilda Agustin Detuage; Henny Welsa; Ambar Lukitaningsih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research was conducted in Yogyakarta, this research aims to analyze the influence of brand ambassadors, brand imagewith customer trust as an intervening factor in the purchase decision of skintific users in Yogyakarta. This study is a quantitative study. The population in this study were young people in Yogyakarta, the sample used was 130 respondents with a purposive sampling technique. The criteria for respondents in sampling were consumers who had purchased Skintific, were domiciled in the city of Yogyakarta and were 17 years old and over. The data collection technique in this study used a questionnaire. The data analysis technique used the Classical Assumption Test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T test, F test, coefficient of determination test and Sobel test. The results of this study indicate that Brand Ambassador has a significant negative effect on the Purchase Decision of skintific products. Brand Ambassador has a positive effect on Customer Trust of Skintific products. Brand Image has a positive effect on Customer Trust of skintific products. Customer Trust has a significant negative effect on Purchase Decision of skintific products. Brand Image has a significant negative effect on Purchase Decision of skintific products.